HUBUNGAN MEDIA SOSIAL TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR MATEMATIKA - Gladys Yuanita Dwi Hartanto; Janice Gouw; Junita Junita; Violent Hennyta (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Along with the development of technological advances, social media is increasingly diverse. Social media such as Instagram, Facebook, Youtube are widely used by all ages including elementary school students. Easy access and use make social media look attractive to use. Its use is not only to find learning materials, but can be used to communicate with anyone they meet from the platform. Researchers wanted to know how the influence of social media and learning motivation on the mathematics learning outcomes of grade VI students at SD XYZ. Researchers use a quantitative approach to process data obtained by correlative descriptive methods. The respondents who were the object of the study were grade VI students at SD XYZ as many as 30 students. Data collection techniques by filling out questionnaires on social media use and learning motivation through the Google Form application, while for learning outcomes researchers took data from several math task scores. The data obtained is processed with the SPSS v25 program. The results showed (1) there was no significant influence of social media use on mathematics learning outcomes, (2) there was no significant enough influence between learning motivation and mathematics learning outcomes, (3) there was no positive and significant relationship between social media use and learning motivation simultaneously with mathematics learning outcomes.